2018
DOI: 10.1186/s12969-018-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for damage in childhood-onset systemic lupus erythematosus in Asians: a case control study

Abstract: BackgroundAccumulated damage is an important prognostic factor in systemic lupus erythematous. However, the pattern of disease damage and its risk factors have not been well studied in childhood-onset systemic lupus erythematosus (cSLE) in Asia. The objectives are to evaluate the pattern of damage and to identify the risk factors for accumulated damage in an Asian group of cSLE.MethodsA retrospective chart review was conducted on a group of 59 patients with cSLE. Patient demographics and clinical variables wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
5
24
1
Order By: Relevance
“…One study demonstrated that there is a positive correlation between SDI score and the number of recurrent major infections in pediatric-onset SLE [47]. Sit et al also reported that disease damage was signi cantly associated with a greater number of episodes of major infection [48]. These nding are in consistent with our study the associated between SDI with infection (P < 0.0001) by using multivariate GEE.…”
Section: Discussionsupporting
confidence: 92%
“…One study demonstrated that there is a positive correlation between SDI score and the number of recurrent major infections in pediatric-onset SLE [47]. Sit et al also reported that disease damage was signi cantly associated with a greater number of episodes of major infection [48]. These nding are in consistent with our study the associated between SDI with infection (P < 0.0001) by using multivariate GEE.…”
Section: Discussionsupporting
confidence: 92%
“…Our cohort exhibited a higher female to male ratio (7.3:1) in comparison with other childhood lupus cohorts with a typical female to male ratio of 5.6:1 and had a younger median age of diagnosis at 10.3 years with the majority (88.6%) having disease onset before the age of 12 years. 2,16,19,20 However, the age-related gender differences normally seen in other paediatric cohorts was similarly seen in our cohort with a female to male ratio of 2.3:1 in the under 5s and 15:1 in those with pubertal or post-pubertal onset. 3,20,21 Compared with other reported data, our male patients were not significantly younger at diagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…To the best of our knowledge, this is the largest pediatric study to date on the association between SLE and AVN. Overall, 2.6% of our patients demonstrated evidence of symptomatic AVN, which is lower than in previous studies (ranging from 5.4 to 40%) [15][16][17][18][19][20][21] but similar to the 3.1% reported by Bogmat et al 22 Affected individuals can be asymptomatic in the early stages of disease, and are detected by magnetic resonance imaging. Therefore, the true prevalence rate in our cohort is likely to be higher as only symptomatic cases who sought medical care were identified.…”
Section: Discussionsupporting
confidence: 47%